PREPARATION AND PHYSICOCHEMICAL ANALYSIS OF NISHA AMALAKI - AN AYURVEDIC FORMULATION (International Journal of Ayurveda and Pharma Research, 2016)
Samskara is one of the important processes in preparation of Ayurvedic formulations. It enhances the medicinal property of the formulation and attains maximum potency to cure the diseases. Ayurvedic texts describe many formulations for different ailments. Nisha amalaki is reputed for treating diabetes and its complication conditions. This formulation has been considered complementary medicine or alternative to conventional medicines across the globe.This formulation consisting of two potent herbs namely Haridra and Amalaki mentioned in Caraka Chikitsa. Amalaki (Emblica officinalis), belongs to family Euphorbiacae is one of the ingredient in Nishamalaki churna, This drug is used for the purpose of rejuvenation, aphrodisciac, cures tiredness, bleeding disorder, Diabetes mellitus, eye disorder etc. The other and main ingredient of Nishamalaki is Haridra (Curcuma longa), belong to family Zingebearaceae which is recommended for treating the skin disorder, diabetes mellitus etc. The concept of Samaskara has been explained in Caraka samhita vimana sthana for the transmigration of Gunas better therapeutic effect of the drugs. The present work deals with preparation of Nisha Amalaki by doing Bhavana samskara as mentioned in ancient texts including raw drug procurement and preparation. Hence this polyherbal formulation needs science-based approach toward manufacturing process and chemical standardization.